Vision-based verification of authentic JAKIM halal logo - Razali, Sumirah; Isa, Nurul; Htike@Muhammad Yusof, Zaw Zaw; Nyein Naing, Wai Yan (2015)
In Malaysia, the authenticity of halal logo has been a great concern to its Muslim community due to the existence of different types of halal logo in the market. Due to this situation, in this paper, a detection system was developed to classify the authentic Jabatan Kemajuan Islam Malaysia (JAKIM) halal logo from the unauthentic ones. All the distinct features from the authentic logo were used in the implementation part of this project with the intention of producing a reliable detection system. The methods that are chosen to be used are SURF, SIFT, GIST, and k-means. These methods can be said is reliable and practical as the resulted accuracy which was 86.6667 was quite high.